PHILOSOPHICAL INTERPRETATION OF THE IDEAS OF MORALITY AND JUSTICE IN THE WORKS OF KHONDAMIR (Scientific journal of the Fergana State University, 2026)
This article examines the views of the prominent 16th-century historian and philosopher Khondamir on the concepts of morality and justice from a philosophical perspective. The author analyzes the moral and spiritual foundations of human perfection, emphasizes the necessity of establishing justice as a basis for social order, and reveals the philosophical essence of the interrelation and harmony between morality and justice in human society.